PPC: Privacy-Preserving Chatting in Vehicular Peer-to-Peer Networks - Xiaohui Liang; Rongxing Lu; Xiaodong Lin; Xuemin Shen (2010 IEEE 72nd Vehicular Technology Conference - Fall, 2010)
In this paper, a privacy-preserving chatting scheme is proposed to secure vehicular communication and achieve user privacy preservation in vehicular peer- to-peer networks. In specific, we first introduce identity-based-encryption technique which can protect the confidentiality of chatting content. Furthermore, to preserve user privacy, our scheme employs ring signature technique, which not only provides message authentication but also guarantees unconditional source anonymity. With the proposed scheme, vehicles change their pseudo identities periodically and make attackers unable to link users' transactions in different periods. As a result, the proposed scheme can achieve data confidentiality, efficient authentication, and privacy violation elimination. In addition, through detailed security and efficiency analyses, it is demonstrated the proposed scheme resists most of existing attacks in vehicular peer-to-peer networks and provides efficient sending and receiving operations.